Mathematical and Experimental Modelling of Adsorption in Fixed Bed. II. Experimental Investigation of Nonisothermal Single Solute Adsorption and Adsorber Simulation - P. Rajniak; J. Ilavský (Adsorption Science & Technology)
The adsorption separation process of n -heptane on a molecular sieve in a fixed bed adsorber is investigated. Experimental concentration and temperature breakthrough curves are obtained using different gas inlet concentration and temperature, different bed length and gas mixture flow rate. The mentioned experimental data are simulated a priori by means of a two-phase mathematical model. The model parameter values used in the simulations are estimated either through available semiempirical correlations or by independent experimental runs. An example of predicted and experimental concentration and temperature breakthrough curves comparison is presented.